2007
DOI: 10.1128/aac.01187-06
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Campylobacter jejuni and Campylobacter coli Clinical Isolates from Poland

Abstract: We tested 102 Campylobacter jejuni and 6 Campylobacter coli clinical isolates from Poland. All were susceptible to erythromycin. Among the tested C. jejuni isolates 55.9% and 13.7% were resistant to ciprofloxacin and tetracycline, respectively. Replacement of Thr86 with Ile in GyrA and a plasmid-borne tet(O) gene were the main resistance mechanisms for fluoroquinolones and tetracycline, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
8
14
2
3
Order By: Relevance
“…In our study, resistance tonalidixic acid was 3 (%33.3, which is similar to Ibrahim et al (24) report (23%) and two different studies from Thailand (77% (25) and 84% (26)), whereas resistance to erythromycin was 77.7% whichconflicts with Salehi et al (0%) (14) and Ibrahim and Wardak (0%) (24,27) reports, but is similar to Nonga and Muhairwa reports (28) which showed that 20% -50% of isolates were resistant to erythromycin and gentamicin. The resistance rate of our isolates to tetracycline was 77.7% that conflicts with the resistance rate reported in Poland (13.7%), but is similar to the results of Alberta in Canada (50%) and Spain (72%) (20,29).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, resistance tonalidixic acid was 3 (%33.3, which is similar to Ibrahim et al (24) report (23%) and two different studies from Thailand (77% (25) and 84% (26)), whereas resistance to erythromycin was 77.7% whichconflicts with Salehi et al (0%) (14) and Ibrahim and Wardak (0%) (24,27) reports, but is similar to Nonga and Muhairwa reports (28) which showed that 20% -50% of isolates were resistant to erythromycin and gentamicin. The resistance rate of our isolates to tetracycline was 77.7% that conflicts with the resistance rate reported in Poland (13.7%), but is similar to the results of Alberta in Canada (50%) and Spain (72%) (20,29).…”
Section: Discussionsupporting
confidence: 91%
“…The resistance rate of our isolates to tetracycline was 77.7% that conflicts with the resistance rate reported in Poland (13.7%), but is similar to the results of Alberta in Canada (50%) and Spain (72%) (20,29). All the isolates of C. jejuni were resistance to ciprofloxacin, whereas Wardak et al (27) reported 55.9%. Hoge et al (26) reported an increase in ciprofloxacin resistance among Campylobacter species from 0 in 1991 to 84% in 1995 in Thailand, which is similar to our report.…”
Section: Discussionsupporting
confidence: 65%
“…Studies conducted in Poland in the years 2003e2005 on C. jejuni isolates from humans indicated that 55.9% of the strains were resistant to ciprofloxacin (Wardak, Szych, Zasada, & Gierczy nski, 2007). The tetracyclines, being broad spectrum antibiotics, are among the most frequently used therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…Dada esta situación, es válido suponer que la probabilidad de que este tipo de resistencia haya sido adquirida "intra-tratamiento" es baja, pudiendo asumir que la infección ha sido provocada por bacterias previamente resistentes [13][14] . Diversas publicaciones han asociado el aumento de la resistencia de Campylobacter a las quinolonas con la introducción de estos fármacos en la industria avícola, principalmente enrofloxacina, cuyo metabolito activo es ciprofloxacina 17,21,29,30 . A pesar de que en nuestro país se realiza una vigilancia de los niveles permitidos de este medicamento en la industria avícola, no existen publicaciones sobre la resistencia de cepas de Campylobacter aisladas de aves para consumo humano.…”
Section: Discussionunclassified
“…Dada la progresiva resistencia a quinolonas reportada en el mundo [13][14][15][16][19][20][21][22] , el objetivo de nuestro trabajo fue conocer la susceptibilidad antimicrobiana de C. jejuni a los fármacos utilizados de forma empírica en el tratamiento de la diarrea aguda.…”
Section: Microbiología Clínicaunclassified